THE ROLE OF ARTIFICIAL INTELLIGENCE IN TEACHING ENGLISH LANGUAGE - Imamaliyeva Gulnoza (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the role of artificial intelligence (AI) in teaching English. It discusses how AI technologies provide personalized learning, interactive practice, real- time feedback, and efficient assessment for language learners. The study highlights the advantages of AI in enhancing student engagement, supporting teachers, and improving learning outcomes. Additionally, the article examines how AI tools can promote motivation, encourage autonomous learning, and facilitate access to global English learning resources. While AI is a powerful educational tool, it should be integrated alongside human instruction to ensure a balanced and effective English learning experience.